Post-COVID-19 Transition in University Physics Courses: A Case of Study in a Mexican University - Francisco Delgado (MDPI AG, 2022)
The extended confinement imposed by the COVID-19 pandemic lockdowns resulted in the imposition of online education for two years. Many students experienced their transitions to higher educative levels during this time, surely losing some academic learning as a consequence. On the other hand, this context could have promoted different types of competencies, until recently not explored, as a function of students' personalities or academic profiles. Physics teaching is among those areas which have changed from its traditional methods during this period. The return to school during the 'New Normal' has resulted in certain concerns about students' adaptability due to their possible lack of learning over this time. We analyse, in the current research, the transitions of three generations crossing several pandemic stages during their time participating in university physics courses during the first year, a common entry point for engineering programs. In addition, we analyse several academic traits as causal factors of academic success in order to understand how performance could be affected during online education and during the 'New Normal'. The results highlight a general high level of adaptation for the most of the students, but still, some of them were affected in terms of the functioning of their learning styles or regarding their personality profiles. Notably, no meaningful losses were detected among the last transition; instead, several interesting aspects were found relating to academic profile appearing to have an effect on the students' performance during the first transition to online education, and then during the second transition back to face-to-face education in the 'New Normal'.